Combustion synthesis and characterization of NiO nanoparticles. (December 2015) - Ramasami, Alamelu K.; Reddy, M.V.; Balakrishna, Geetha R.
Abstract: Nickel oxide nanoparticles (NiO NPs) have been prepared by gel-combustion technique using 1:0.5 (N 105) and 1:1 (N 11) weight ratios of oxidizer, nickel nitrate hexahydrate and fuel, cassava starch, respectively. The X-ray diffraction pattern of the samples revealed cubic phase of nickel oxide and the average crystallite size of 28 and 38 nm for N 105 and N 11, respectively, were noted. In comparison to particle size measured using TEM (35 and 60 nm), the average particle size obtained from DLS (250 and 350 nm) was larger for N 105 and N 11, respectively. NiO NPs were found to have indirect band gap (2.98 and 2.3 eV) as revealed by optical spectroscopy. They were tested for energy storage, antimicrobial activity and photocatalytic applications. Electrochemical studies showed NiO NPs had a reversible capacity of 940 and 785 mA h/g for N 105 and N 11, respectively and they retained a capacity of 59% and 47% upto 50 cycles. The antimicrobial activity was tested against two bacterial strains and a fungal strain. The photocatalytic activity was measured for degradation of methylene blue in ultra-violet as well as sunlight. NiO, obtained by using 1:1 oxidizer to fuel ratio, (N 11) exhibited 94% degradation efficiency in sunlight because of a visible light-active band gap (2.3 eV). Graphical abstract: